ANALISIS PELAKSANAAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA PADA SISWA KELAS V SEKOLAH DASAR NEGERI PASAR KLIWON SURAKARTA - Endah Utami, Moefty Mahendra, Sri Mulyati (CV. ADIBA AISHA AMIRA, 2024)
This research aims to find out how the Project for Strengthening the Profile of Pancasila Students is implemented in the mutual cooperation dimension in class V at Pasar Kliwon State Elementary School. This research method uses descriptive qualitative methods. Location at Pasar Kliwon State Elementary School, Surakarta. The data collection techniques used were observation, interviews and documentation. The results of this research can be concluded that the teacher has implemented the dimensions of mutual cooperation well. It can be seen in project planning that the teacher prepares a project module which contains the project objectives and dimensions of mutual cooperation including the values ​​of collaboration, caring and sharing. In implementing the project, the dimension of mutual cooperation is conveyed, which includes the collaboration aspect, which can be seen when students in groups coordinate and work together in working on the project. In the caring aspect, good relationships and a sense of empathy can be seen among students, such as lending each other tools, being responsive to friends' difficulties and positive interdependence. The sharing aspect is fostered by teaching students to give and receive something valuable. At the project evaluation stage, process evaluation is used through observations during project activities.